Improving agri-food sector productivity in Indonesia through information and communication technologies - Endiarjati Dewandaru Sadono; Ilham Unggara (Asian Development Bank Institute (ADBI), 2024)
The productivity of Indonesian agri-food, especially rice, has been declining over the last decade. A decreasing emphasis on technology innovation and dissemination has been cited as a possible cause of this problem. Information and communication technologies (ICTs) can play a crucial role in improving this productivity problem. This study provides an assessment of whether ICT utilization in the form of social media, e-commerce, and farm management can improve rice farm productivity in Indonesia. Based on observations of 149 farmers in Yogyakarta and Jawa Tengah provinces, Indonesia, this study finds that social media adoption by rice farmers is more prevalent than e-commerce and farm management apps. Social media can complement the function of face-to-face extension services provided by the government. Moreover, social media adoption by farmers can increase farm productivity, knowledge of organic fertilizer benefits, and organic fertilizer adoption as well as credit access. Nevertheless, there are still huge barriers to e-commerce adoption, such as dependence on intermediaries in selling their products and a lack of knowledge on how to use the application. With regard to farm management apps, this study finds important aspects and features that can be considered in developing this kind of app in the future. Based on these findings, we offer several policy recommendations, such as expanding the adoption of social media among young farmers, increasing education on the benefits and on how to use e-commerce, and conducting further research to develop farm management apps.
Keywords: DO4; D24; D83; 330; farmers; information; social media; e-commerce; farm management apps; Indonesia